Reinforcing three-dimensional self-reinforcing self-etch adhesive and surface conditioning in immediate dentin sealing of composite resin–dentin - Poppy Andriani; Ade Prijanti Dwisaptarini; Eko Fibryanto; Rosalina Tjandrawinata; Siriwan Suebnukarn (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Exposed dentin must be sealed with a dentin bonding agent immediately after tooth preparation, described as immediate dentin sealing (IDS). The purpose of IDS is to prevent dentin contamination during temporary restorations, reduce dentin hypersensitivity, and improve bond strength. Self-etch (SE) adhesive can be easily removed during surface treatment before cementation in the IDS technique. Reinforced SE adhesive with an additional layer of flowable composite significantly increases bond strength. Purpose: This study aimed to determine the effects of reinforcing one-bottle SE adhesive with a three-dimensional self-reinforcing monomer and surface conditioning with air abrasion and pumice on the bonding of composite resin to dentin in the IDS technique. Methods: Thirty-six human premolars were selected and randomly divided into three groups. Each group was divided into two sub-groups (n = 6) according to the adhesive system and surface conditioning. All samples were restored with 3 × 3 × 3 mm composite resin before being tested for shear bond strength. The data were analyzed with two-way ANOVA and Sidak’s multiple comparison test (p < 0.05). Results: There were significant differences between groups. Total-etch with pumice showed a higher mean value of shear bond strength than SE with air abrasion. Conclusion: The use of air abrasion in the IDS technique with SE adhesive affects the shear bond strength of dentin. Surface conditioning with air abrasion or pumice with SE adhesive showed the lowest mean values compared with SE adhesive with an additional layer of flowable composite resin.